The sugar and energy in non-carbonated sugar-sweetened beverages: a cross-sectional study - Chuyao Jin; Lizi Lin; Chenxiong Li; Yuanzhou Peng; Graham A. MacGregor; Fengjun He; Haijun Wang (BMC, 2019)
Abstract Background The consumption of non-carbonated sugar-sweetened beverages (NCSSBs) has many adverse health effects. However, the sugar and energy content in NCSSBs sold in China remain unknown. We aimed to investigate the sugar and energy content of NCSSBs in China and how these contents were labelled. Methods A cross-sectional survey was conducted in 15 supermarkets in Haidian District, Beijing from July to October 2017. The product packaging and nutrient information panels of NCSSBs were recorded to obtain type of products (local/imported), serving size, nutrient contents of carbohydrate, sugar and energy. For those NCSSBs without sugar content information, we used carbohydrate content as a replacement. Results A total of 463 NCSSBs met the inclusion criteria and were included in our analysis. The median of sugar content and energy content was 9.6 [interquartile range (IQR): 7.1-11.3] g/100 ml and 176 (IQR: 121-201) kJ/100 ml. The median of sugar contents in juice drinks, tea-based beverages, sports drinks and energy drinks were 10.4, 8.5, 5.0 and 7.4 g/100 ml. Imported products had higher sugar and energy content than local products. There were 95.2% products of NCSSBs receiving a 'red'(high) label for sugars per portion according to the UK criteria, and 81.6% products exceeding the daily free sugar intake recommendation from the World Health Organization (25 g). There were 82 (17.7%) products with sugar content on the nutrition labels and 60.2% of them were imported products. Conclusions NCSSBs had high sugar and energy content, and few of them provided sugar content information on their nutrition labels especially in local products. Measures including developing better regulation of labelling, reducing sugar content and restricting the serving size are needed for reducing sugar intakes in China.